Chemoprevention of Gastric Cancer: Statins - Sang Hyeon Choi; Gwang Ho Baik (Yong Chan Lee, 2017)
Gastric cancer is one of the leading causes of cancer-related deaths worldwide. Because the gastric cancer-related mortality rate is expected to increase, chemo-preventive strategies for gastric cancer are required. Statins inhibit 3-hydroxy-3-methylglutaryl coenzyme A reductase, the enzyme involved in the rate-limiting step in cholesterol synthesis. Several studies have shown that statins have potential protective effects against gastric cancer; however, other studies have reported contradictory results. Therefore, further studies are needed to clarify the role of statins in the chemoprevention of gastric cancer.